Structure-Guided Mechanisms Behind the Metabolism of 2,4,6-Trinitrotoluene by Glutathione Transferases U25 and U24 That Lead to Alternate Product Distribution - Tzafestas, Kyriakos; Ahmad, Laziana; Dani, M. Paulina; Grogan, Gideon; Rylott, Elizabeth L.; Bruce, Neil C. (Frontiers in Plant Science, 2018)
The explosive xenobiotic 2,4,6-trinitrotoluene (TNT) is a major worldwide environmental pollutant and its persistence in the environment presents health and environmental concerns. The chemical structure of TNT dictates that biological detoxification pathways follow predominantly reductive transformation of the nitro groups, and as a result, TNT is notoriously recalcitrant to mineralization in the environment. Plant-based technologies to remediate this toxic pollutant rely on a solid understanding of the biochemical detoxification pathways involved. Towards this, two Arabidopsis Tau class glutathione transferases, GSTU24 and GSTU25, have been identified that catalyze the formation of three TNT-glutathionylated conjugates. These two GSTs share 79 % identity yet only GSTU25 catalyzes the substitution of a nitro group for sulfur to form 2-glutathionyl-4,6-dinitrotoluene. The production of this compound is of interest because substitution of a nitro group could lead to destabilization of the aromatic ring, enabling subsequent biodegradation. To identify target amino acids within GSTU25 that might be involved in the formation of 2-glutathionyl-4,6-dinitrotoluene, the structure for GSTU25 was determined, in complex with oxidized glutathione, and used to inform site-directed mutagenesis studies. Replacement of five amino acids in GSTU24 established a conjugate profile and activity similar to that found in GSTU25. These findings contribute to the development of plant-based remediation strategies for the detoxification of TNT in the environment. Key words: 2,4,6-Trinitrotoluene; TNT; Arabidopsis; Glutathione Transferase; GST; Detoxification; Xenobiotic.